VISI SPIRITUAL MASYARAKAT BANJAR - Noor, Irfan (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2013)
This article aims to explain the influences of sufism on Banjarese culture. The description is regarded important owing to tha fact that first arrival of Islam in this region in 16th century can be not separated from the role of sufism and sufi orders in Islamic intellectual discourses in Indonesia commonly. The existence of Islam, therefore, as etnic identity of this society necessarily was coloured of sufism in its character. This article concludes that the influences of sufism on Banjarese culture were reflected in social attitudes towards traditional ceremonies and social costums based on religious spiritual background.